Seminal fluid production and sperm packaging in dromiid crabs (Brachyura, Podotremata) - Garcia Bento, Maria Alice [UNESP]; López Greco, Laura S.; Zara, Fernando José [UNESP] (Elsevier, 2019)
Reproductive anatomy, including sperm storage structures and sperm transfer, is an important feature used to analyze phylogenetic relationships among taxa. We describe the male reproductive anatomy, seminal fluid production and packaging of spermatozoa in the vas deferens of primitive crabs. In all species of Dromiidae, the testes were tubular type and the vas deferens is a tube with a simple epithelium. The spermatozoa are in a central mass immersed in type I secretion, forming a large spermatic cord. In Moreiradromia antillensis and Dromia erythropus the spermatic cord is surrounded by a more complex secretion layer composed by protein granules and polysaccharides that seem to be responsible to form the sperm plaque which was absent in Hypoconcha. The sperm plaque was found in all Dromiinae species, which may result from the mating and probably act as a barrier to subsequent copulations. These patterns of elongated coenospermic spermatophore found here are unique and different from the spermatophores of all true crabs and may be considered a plesiomorphic state to spermatophoric structure in Brachyura. Our results show a novel type of spermatozoa packaging and new insights into how sperm might be transferred in Podotremata.
Keywords: anatomy; Hypoconcha; male reproductive system; spermatheca; ultrastructure